Common Trace Fossils of the Deltaic and Turbidite Outcrops in Kutei Basin, East Kalimantan: A Field Note - Herman Darman (Ikatan Ahli Geologi Indonesia, 2004)
The Kutei Basin is dominantly clastic Tertiary basin bounded by basement uplifts in the north, west and east. The basin is open towards the Makassar Strait in the east. The Paleogene sections of the basin were outcropped at the basin margin. In Muara Wahau area in the northern part of the basin, this section is dominated by turbidites with slump features. High variety and low quantity of trace fossils are found in the thin-bedded turbidites, mostly grazing structures and the assemblage suggest Nereites ichnofacies. The trace fossil associations suggest ocean basin environment of deposition and the biostratigraphic analysis indicates bathyal to abyssal zone. At the centre of the basin the Neogene deltaic sections cropped well in Samarinda area. there is high quantity of trace fossils but low in variety. Dwelling vertical burrows of Skolithos ichnofacies are dominant in this section. The trace fossil association suggests tidal zone with inner to outer neritic biostratigraphic environment.